Strategi Pembiasaan Pronunciation untuk Membentuk Kebiasaan Berbicara Bahasa Inggris di SMKN 3 Palangka Raya - Nabila Nur Azizah; Sabarun Sabarun (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aimed to enhance English pronunciation skills and establish a consistent speaking habit among students of SMKN 3 Palangka Raya. Thirty-six students of class X TKJ (Computer and Network Engineering) participated in a one-month program using thematic sentence templates, repetitive pronunciation drills, and self-reflection through voice recording feedback. The implementation employed a participatory and descriptive-qualitative approach, involving active collaboration between facilitators, teachers, and students throughout all stages. Weekly themes included self-introduction, daily activities, hobbies, and opinions to create a contextual and meaningful learning situation relevant to students’ daily lives. The results showed noticeable improvement in pronunciation clarity, increased awareness of pronunciation errors, and higher confidence in speaking English during classroom activities. However, aspects such as fluency and vocabulary variation remained limited due to the short duration of the program. Overall, the pronunciation habituation strategy proved effective in fostering awareness, comfort, and sustainable speaking habits when applied consistently over a longer period.